Novel Synthesis of 3-Aryl-4-hydroxybenzofurans via Four-Component Reaction from Substituted Nitrostyrenes, Aromatic Aldehydes, Cyclohexan-1,3-diones, and Ammonium Acetate - Li, Yan; Liu, Hui; Sun, Liang; Liu, Juanjuan; Xue, Zhiheng; Yao, Juan; Wang, Cunde (Synlett, 2013)
An one-pot-reaction methodology was developed to synthesize a variety of polysubstituted 3-aryl-2-arylmethylene amino-4-hydroxybenzofurans from substituted β-nitrostyrenes, aromatic aldehydes, ammonium acetate, and cyclohexane-1,3-diones for the generation of a wide range of structurally interesting and pharmacologically significant compounds. The reaction pathway involves Michael addition of substituted nitrostyrenes and cyclohexane-1,3-diones, then nucleophilic addition of 2-(2-nitro-1-phenylethyl)cyclohexane-1,3-dione and Schiff base generated from aromatic aldehyde and ammonium acetate and intramolecular cyclization, followed by dehydroaromatization to afford the corresponding 3-aryl-2-arylmethyleneamino-4-hydroxybenzofurans.
Keywords: multicomponent reaction; 4-hydroxybenzofuran; substituted β-nitrostyrene; dehydroaromatization; cyclohexane-1,3-dione